A NARRATIVE STUDY OF TEACHERS’ BELIEFS IN ONLINE SPEAKING CLASS - Rachel Bona Uly (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine teachers' beliefs in conveying communicative EFL teaching during the pandemic. The current research is ground by the restrictions in the form of learning hours and other factors on distance learning that affect the communicative teaching principles which is usually occur in offline class. Therefore, it is important to understand teachers' beliefs by understanding how teachers overcome the limitations related to the speaking practices and language skills of students in online learning. A qualitative narrative inquiry research design will be use as relevant method for this study. This research design enabled the researchers to gather data into a descriptive data analysis. The data will obtain firstly by describing the three EFL teachers’ interaction with learners in speaking online class, then explores the teachers' beliefs about speaking practice in interviews. In addition, undemandings questionnaires is also necessary to engage as effective secondary data to strengthen primary data. Thematic analysis is requiring for this study to identified, analysed, and coded participants' responses to voice their beliefs. These findings provide an opportunity to understand the potential role of beliefs in shaping communicative online learning. This investigation tracked down that talking practice is molded by different convictions held by educators, not just identified with their need to apply an informative learning, yet in addition the significance of showing language and different viable obstructions in internet learning classes.